THE ASSESSMENT OF NURSE’S KNOWLEDGE, ATTITUDE, AND PRACTICES REGARDING NUTRITIONAL MANAGEMENT OF DIABETES MELLITUS - HAIDER , A; SADDIQUE , H; TASNEEM , SS (Biological and Clinical Sciences Research Journal, 2024)
Effective nutritional management is critical in diabetes care, requiring healthcare professionals, particularly nurses, to possess adequate knowledge, attitudes, and practices (KAP). This study evaluates the KAP of nurses regarding diabetes nutritional management in a tertiary care hospital in Pakistan. Objective: To assess nurses' knowledge, attitudes, and practices regarding the nutritional management of diabetes mellitus and identify gaps for targeted interventions. Methods: A descriptive cross-sectional study was conducted among 134 nurses using a structured questionnaire. Data were analyzed using SPSS version 26, with descriptive statistics summarizing results. Results: The majority of nurses (79.1%) demonstrated knowledge of balanced diets for diabetic patients, though only 48.5% understood that diabetics should not exclude any nutrient. While 38.1% consistently assessed patients' nutritional needs, documentation of nutritional diagnoses was low (9%). Attitudes were mixed, with only 32.8% strongly agreeing that diet plays a critical role in glycemic control. Conclusion: Nurses demonstrated strong foundational knowledge and positive practices but showed misconceptions and mixed attitudes toward nutritional management of diabetes. Addressing these gaps through targeted training and institutional support can enhance diabetes care and improve patient outcomes.